2020
DOI: 10.1007/s40726-020-00140-w
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Green Algae in Surface Water: Problems and Opportunities

Abstract: Purpose of ReviewCyanobacteria, commonly known as blue-green algae, are often seen as a problem. Their accumulation (bloom) in surface water can cause toxicity and aesthetic concerns. Efforts have been made in preventing and managing cyanobacterial blooms. By contrast, purposeful cultivation of cyanobacteria can create great opportunities in food, chemical and biofuel applications. This review summarises the current stage of research and the socio-economic impacts associated with both the problems and opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 129 publications
1
14
0
Order By: Relevance
“…A quite similar result was reported by Gao et al [15]. They demonstrated that 25 min treatment was adequate for 100% M. aeruginosa removal at 5 mA/cm 2…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A quite similar result was reported by Gao et al [15]. They demonstrated that 25 min treatment was adequate for 100% M. aeruginosa removal at 5 mA/cm 2…”
Section: Discussionsupporting
confidence: 88%
“…As a result of rapid oxygen consumption, hypoxic conditions develop, resulting in plant and animal die-off in water bodies [1]. These blooms are a threat to the drinking water supply owing to their potential toxicity and the release of taste and odor compounds such as geosmin and 2-methyl-isoborneol (2-MIB) [2,3]. Generally, cyanobacteria release a large amount of soluble algogenic organic matter (AOM) to the water such as extracellular organic matter (EOM), which is expelled to the water by living algal cells as a product of their metabolic activities, and intracellular organic matter (IOM), which is secreted upon the rupture of cells caused by endogenous or exogenous factors [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria are recognized as a threat to surface water quality because they can form dense blooms and produce secondary metabolites including taste and odor compounds (e.g., geosmin, 2-methyl isoborneol) and potent cyanotoxins (Harke et al, 2016;Huisman et al, 2018;Paerl, 2014;Vu et al, 2020). As a result of anthropogenic activities, cyanobacterial bloom frequency and intensity have been increasing (Huisman et al, 2018); climate change-exacerbated landscape disturbances (e.g., wildfires) further promote their proliferation (Emelko et al, 2016;Silins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many cyanobacterial species produce toxins and release them into the water, making them unsuitable for drinking and recreational use. Blooms cause economic damage by affecting tourism, agriculture [ 8 ], and aquaculture industries [ 9 ]. However, cyanobacterial blooms are not an ecological endpoint, but rather an intermediary [ 10 ]; they cause changes in biodiversity and functionality of other communities [ 11 , 12 ], but also respond to changes in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%